2000
DOI: 10.1207/s15327914nc3601_14
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Interferes With Cell Cycle Progression and Insulin-Like Growth Factor I Signaling in Mammary Cancer Cells

Abstract: Recent studies have shown that high insulin-like growth factor I (IGF-I) blood level is a risk factor in breast and prostate cancer. The aim of this study was to determine whether the mitogenic activity of IGF-I in mammary cancer cells can be reduced by the dietary carotenoid lycopene. The anticancer activity of lycopene, the major tomato carotenoid, has been suggested by in vitro, in vivo, and epidemiological studies. Growth stimulation of MCF7 mammary cancer cells by IGF-I was markedly reduced by physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
2
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(147 citation statements)
references
References 46 publications
6
134
2
3
Order By: Relevance
“…In three of these studies, higher intake of cooked or processed tomatoes or lycopene was associated with either lower IGF-I levels [14], higher IGFBP-3 levels [22], or a lower IGF-I/IGFBP-3 molar ratio [18]. Two in vitro studies have shown that lycopene can inhibit IGF-I-stimulated growth of endometrium and mammary cancer cell lines [34,35]. In these studies, lycopene reduced IGF-I receptor signaling, and increased levels of membrane-associated IGFBPs [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In three of these studies, higher intake of cooked or processed tomatoes or lycopene was associated with either lower IGF-I levels [14], higher IGFBP-3 levels [22], or a lower IGF-I/IGFBP-3 molar ratio [18]. Two in vitro studies have shown that lycopene can inhibit IGF-I-stimulated growth of endometrium and mammary cancer cell lines [34,35]. In these studies, lycopene reduced IGF-I receptor signaling, and increased levels of membrane-associated IGFBPs [35].…”
Section: Discussionmentioning
confidence: 99%
“…Two in vitro studies have shown that lycopene can inhibit IGF-I-stimulated growth of endometrium and mammary cancer cell lines [34,35]. In these studies, lycopene reduced IGF-I receptor signaling, and increased levels of membrane-associated IGFBPs [35]. Lycopene supplementation also increased plasma IGFBP-3 concentrations in ferrets [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evident from in vitro and animal studies, purified lycopene may inhibit prostate cancer growth only at higher concentrations, in comparison with tomato antioxidant supplementation. Karas et al (2000) have further reported inhibitory effects of lycopene on MCF7 human mammary cancer cell growth, owing to interference in IGF-1 receptor signaling and cell cycle progression (Karas et al, 2000). Thus, interference in androgen metabolism, and inhibition of growth factors and cytokine activity, appear to be the major pathways through which lycopene inhibits prostate and breast cancer growth.…”
Section: Mechanisms Of Action Of Lycopenementioning
confidence: 99%
“…A recent systematic review showed circulating IGF-1 to be associated with increased risk of prostate and pre-menopausal breast cancer (Renehan et al, 2004). A number of studies have suggested a link between lycopene and IGF-1-stimulated cell proliferation in vitro (Levy et al, 1995;Karas et al, 2000), and an inverse association has been demonstrated between cooked tomato consumption and circulating IGF-1 concentrations in vivo (Mucci et al, 2001;Gunnell et al, 2003). Other studies have, however, failed to show an association between circulating IGF-1 and lycopene concentrations (Graydon et al, 2003;Vrieling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%